Engulfment and Cell Motility Protein 1 Protects Against DSS-induced Colonic Injury in Mice via Rac1 Activation. (14th September 2018) - Zheng, Xiao-bin; Liu, Hua-shan; Zhang, Long-juan; Liu, Xuan-hui; Zhong, Xiao-li; Zhou, Chi; Hu, Tuo; Wu, Xian-rui; Hu, Jian-cong; Lian, Lei; Deng, Qi-ling; Chen, Yu-feng; et al.
Abstract: Background and Aims: Mucosal healing is an emerging therapeutic goal that could result in clinical remission of inflammatory bowel disease [IBD]. We sought to determine the role of engulfment and cell motility protein 1 [ELMO1] in wound healing in vitro and in vivo and to investigate the underlying pathways. Methods: RNA transcriptome sequencing was performed to detect the expression profiles of mRNA between inflamed tissues and corresponding non-inflamed tissues of IBD patients, followed by Gene Expression Omnibus [GEO] datasets and western blot analysis. The effects of ELMO1 overexpression or knockdown on cell migration and proliferation were determined. The dependence of these effects on Rac1 was assessed using a Rac1 inhibitor [NSC23766] and a Rac1 pull-down assay. We identified the underlying pathways involved by Gene Ontology [GO] analysis. A dextran sulphate sodium [DSS]-induced colitis model was established to evaluate the role of ELMO1 in colonic mucosal healing. Results: ELMO1 was upregulated in inflamed tissues compared with corresponding non-inflamed tissues. ELMO1 overexpression increased cell migration in a Rac1-dependent manner. Depletion of ELMO1, or NSC23766 administration, abolished this effect. GO analysis revealed that ELMO1 overexpression preferentially affected pathways involved in cytoskeletal regulation and wound healing, which was demonstrated by enhanced F-actin staining and increased numbers of extending lamellipodia in cells overexpressing ELMO1. In DSS-induced colitis, systemic delivery of pSin-EF2-ELMO1-Pur attenuated colonic inflammation and promoted recovery from colonic injury. The protective effect of ELMO1 was dependent on Rac1 activation. Conclusions: ELMO1 protects against DSS-induced colonic injury in mice through its effect on epithelial migration via Rac1 activation.